Treatment of Bell’s palsy by combination of Laser and Kabat rehabilitation: a case study - Kale, Asmita Avinash; Suryavanshi, Tejas V.; Thorat, Komal D. (International Journal of Research in Medical Sciences, 2023)
This study examined the role of Kabat Rehabilitation and laser therapy in Bell's palsy patient, and its effectiveness in physical and social function. Individuals with Bell's palsy, which produces the facial mimicry, it’s crucial for rehabilitation of facial muscle paralysis. PNF enforces and encourages the muscular action on the weaker side of the face, it enables patients with Bell's palsy perform better physically and socially. Therefore, the effectiveness of Kabat therapy in conjunction with Laser was proven in this investigation. The study was conducted at the outpatient department (OPD), Neuro Physiotherapy, Dr. APJ AK COPT. Patient received the Kabat rehabilitation therapy, as well as laser therapy. In this study, results were found significant in HBS and FDI scale comparing pre and post scores by progressing from moderate to normal on grading and progression of 30% on FDI scale. Hence, we conclude that this intervention could be an adjunct intervention in rehabilitation of Bell’s palsy. Physiotherapy Program including Laser therapy and Kabat rehabilitation for 3 weeks had shown significant on the treatment of Bell’s palsy. Hence, it has proven that it could be used as an adjunct intervention on patient with Bell’s palsy.